Inflation versus filling-in: why we feel we see more than we actually do in peripheral vision - Odegaard, Brian (Philos Trans R Soc Lond B Biol Sci, 2018)
Do we perceive fine details in the visual periphery? Here, we propose that phenomenology in the visual periphery can be characterized by an inflated sense of perceptual capacity, as observers overestimate the quality of their perceptual inputs. Distinct from the well-known perceptual phenomenon of ‘filling-in’ where perceptual content is generated or completed endogenously, inflation can be characterized by incorrect introspection at the subjective level. The perceptual content itself may be absent or weak (i.e. not necessarily filled-in), and yet such content is mistakenly regarded by the system as rich. Behaviourally, this can be reflected by metacognitive deficits in the degree to which confidence judgements track task accuracy, and decisional biases for observers to think particular items are present, even when they are not. In two experiments using paradigms that exploit unique attributes of peripheral vision (crowding and summary statistics), we provide evidence that both types of deficits are present in peripheral vision, as observers' reports are marked by overconfidence in discrimination judgements and high numbers of false alarms in detection judgements. We discuss potential mechanisms that may be the cause of inflation and propose future experiments to further explore this unique sensory phenomenon. This article is part of the theme issue ‘Perceptual consciousness and cognitive access’.